Asthma in patients with farmer's lung during a five-year follow-up - Kokkarinen, JI; Tukiainen, HO; Terho, Erkki O (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'This study assessed the incidence of asthma in patients with farmer's lung. Methods The study population consisted of 1031 patients who had occupational farmer's lung diagnosed from 1983 to 1988. The cases of farmer's lung were registered in the nationwide Register of Occupational Diseases by the Finnish Institute of Occupational Health, and all the patients in the study had received compensation from the insurance company for an occupational disease. The diagnosis of asthma was based on entitlement to a special refund for asthma medication costs from the national sickness insurance program. Results Seventy-four cases of asthma were found among farmers with farmer's lung up to the end of the 5 years following the year of the diagnosis for farmer's lung. The prevalence of asthma was 1% in the year preceding the diagnosis. In the year of the diagnosis and during the 5 years of follow-up, asthma was diagnosed in an additional 6% of the patients. Conclusions The results of this study confirm previous findings of a low prevalence of asthma before the onset of farmer's lung in small groups of patients. However, the results also indicate that the incidence of asthma increases during the first years after an episode of farmers lung. For example, in the present study, asthma was apparent in 7% of the patients 5 years after the diagnosis of farmers lung.
Keywords: agricultural worker; extrinsic allergic alveolitis; occupational disease